Transformation and fate of pharmaceuticals, personal care products, and per- and polyfluoroalkyl substances during aerobic digestion of anaerobically digested sludge. (1st July 2022) - Li, Yijing; Thompson, Jack; Wang, Zhiyao; Bräunig, Jennifer; Zheng, Qiuda; Thai, Phong K.; Mueller, Jochen F.; Yuan, Zhiguo
Highlights: Fourteen PPCPs and fifteen PFAS were detected and evaluated. Transformation of 12 PPCPs in sludge occurred during post aerobic digestion. PFPeA, PFHxA, PFBS, and PFOS showed significant aerobic formation. Concentrations of four PFAA precursors did not change after aerobic digestion. Aerobic digestion enhanced the sorption of four PPCPs and three PFAAs by sludge. Abstract: Post-anaerobic aerobic digestion (PAAD) is a promising strategy to further reduce the volume and improve the quality of anaerobically digested sludge (ADS). However, the effect of PAAD process on the fate of pharmaceuticals and personal care products (PPCPs) and per- and polyfluoroalkyl substances (PFAS) remains largely unknown. In this study, fourteen PPCPs and fifteen PFAS were detected in ADS and evaluated regarding their fate and transformation in a laboratory aerobic digester operated with a hydraulic retention time of 13 days under 22 ℃. Twelve PPCPs demonstrated significant ( p < 0.05) decrease in their total concentrations (dissolved and adsorbed fractions combined) with six compounds presenting substantial transformation (> 80%) after aerobic digestion. On the contrary, PFAS were not removed and their concentrations were either increased (increasing ratio: 91 – 571%) or consistent in the sludge during PAAD process, suggesting their recalcitrance to post aerobic digestion. More than half of PPCPs and PFAS demonstrated medium to strong sorption onto solids with their solid fraction higher than 50% in the ADS. After PAAD process, sorption of four PPCPs and three PFAAs to solids was enhanced in sludge. Graphical abstract: Image, graphical abstract